Pollen morphology of Meliaceae from Brazilian forest fragments of Cerrado, Brazil - Fernandes, Alicia Dominguez [UNESP] (2025)
Meliaceae, a pantropical family of Sapindales, have genera and species distributed in subtropical regions of the globe, with native representatives in the Brazilian Cerrado. In this study, we analyzed the pollen grains of 11 Brazilian species of Meliaceae, all native to remaining forest fragments of Cerrado, in São Paulo state of Brazil. This study aimed to characterize and describe the morphology of the pollen grains of these species, identifying characteristics that can support future taxonomic studies. Pollen materials were obtained via collections from forest fragments, and are deposited as herbarium exsiccates. The pollen grains were acetolyzed, measured, described, and photographed using light microscopy; pollen grains of selected species were also analyzed under scanning electron microscopy to obtain details of exine ornamentation. The pollen grains of these species are monad, isopolar, of medium size, with circular amb, occasionally subquadrangular, with small to large polar area; prolate spheroidal, oblate spheroidal, subprolate or suboblate; (3)4-colporate, 4-colporate, (3)4-5-colporate, (3)4(5)-colporate, 4-5(6)-colporate, circulaperturate or fossaperturate, with long to short colpi, narrow and wide, with margo; with rounded and rarely tapered ends; with lalongate or circular endoaperture; exine semitectate, microreticulate; or tectate, granulate, psilate-verrucate, or psilate and rarely perforated in the apocolpium. The exine is thin, and the sexine is thicker than the nexine. Although the pollen characters in Meliaceae are very similar, there is data on the apertures and ornamentation of pollen grains that allows the distinction of species. Furthermore, measurements of the ectoapertures and endoapertures can help distinguish the pollen of genera and species of the family, as evidenced in the multivariate analysis.